Exploring the Relationship Between Tourism and Environmental Degradation in Pakistan’s Economy: A Time Series ARDL Modelling Approach - Altaf, Muqtadir; Awan, Ayesha; Rehman, Saif Ur (iRASD Journal of Economics, 2023)
Tourism has received a lot of attention recently, particularly in developing nations that are already dealing with a variety of issues and difficulties. In many parts of the world, there has been a connection between rising tourism and environmental damage. Governments should use economic growth and human activities that increase CO2 emissions, such as energy consumption and tourism, as a proxy for environmental harm in order to limit this. Travel is only one of the damaging behaviors that tourism may engage in that might affect the climate. Global warming and unhealthy air conditions can be exacerbated by networks of transportation. Transit's consequences include environmental disturbance, contamination of the environment, and breathing in pollutants. This study, which spans the years 1997 to 2022 uses Autoregressive Distributed Lag (ARDL) models to examine the long-term cointegrating causal connection among environmental deterioration and tourism. The projected results demonstrate how Pakistan's efforts to stop environmental deterioration are hampered by tourist. GDP and energy consumption are two other important variables that have a long-term, favorably biased connection with carbon emissions. The report advised that lawmakers create a model framework for rules that would oblige the federal government to spend its money in carbon-free or ecotourism enterprises in order to protect a sustainable environment. Moreover, tourism significantly affects the country's economy. Since tourism degrades the environment, regulators must consider both the sector's good and bad effects. In order to protect the environment and encourage sustainable tourism growth in Pakistan's economy, this paper proposes policy recommendations.